PEMBERDAYAAN KADER KESEHATAN MELALUI PELATIHAN KOMUNIKASI EFEKTIF UNTUK OPTIMALISASI IMUNISASI DASAR LENGKAP - Dhimas Herdhianta; Atin Karjatin; Kahar Kahar; Asep Fithri Hilman (Poltekkes Kemenkes Bandung, 2026)
The coverage of Complete Basic Immunization (CBI) among children aged 12–23 months in West Java Province indicates that 2.5% of children did not receive any immunization. This condition reflects that optimal basic immunization coverage has not yet been achieved. One strategy to improve immunization coverage is strengthening the capacity of community health volunteers, particularly in effective communication skills. This effective communication training was conducted in the working area of South Cimahi Community Health Center (Puskesmas Cimahi Selatan) as an empowerment initiative involving 50 community health volunteers to support the optimization of complete basic immunization coverage. The program was implemented through four phases and ten systematically structured steps to ensure the achievement of the training objectives. Participants’ knowledge improvement was evaluated using a pre-test and post-test approach, followed by the Wilcoxon signed-rank test to determine differences in knowledge levels before and after the intervention. The mean knowledge score increased from 77.22 before the training to 84.08 after the training. This represented an average increase of 6.86 points or 8.83%, with a statistically significant difference (p = 0.021; p < 0.05). These findings indicate a significant improvement in the knowledge of community health volunteers following the intervention. Therefore, effective communication training contributes positively to enhancing the knowledge of community health volunteers and is expected to improve their communication skills in promoting complete basic immunization coverage within the working area of South Cimahi Community Health Center.